Supporting the supervisor: organizing professional development to enhance practice. (14th October 2016) - Corrie, Sarah; Lane, David A.
Abstract: Although clinical supervision is deemed central to the delivery and dissemination of high quality CBT, knowledge of what constitutes 'optimal' CBT supervision remains limited. In consequence, understanding of how best to support the development of supervisors is also restricted. This article considers the professional development needs of CBT supervisors, identifying the current context in which CBT supervision is mandated and delivered and seeking to clarify the domains of knowledge, competence and skill that must be mastered. We propose ways in which CBT supervisors might construct their professional development activities and raise questions relating to the need for a more organizationally embedded approach to the development of CBT supervisors in the current professional climate.